Outcomes of Patient Education in Nurse-led Clinics: A Systematic Review - Zohre Pouresmail; Fatemeh Heshmati Nabavi; Najmeh Valizadeh Zare (Journal of Caring Sciences, 2023)
Introduction: Patient education is an independent role of nurses performed in nurse-led clinics (NLCs). The measurement of patient education outcomes validates whether nursing educational interventions have a positive effect on patients, which helps determine whether changes in care are needed. Standardized nursing terminologies facilitate the evaluation of educational outcomes. We aimed to explore the outcomes of patient education in NLCs based on the Nursing Outcome Classification (NOC) system. Methods: The review was conducted according to PRISMA guidelines. We searched "Medline", "Embase", "Web of Science", and "Scopus" databases for articles published between 2000 and 2022. Based on the search strategy, 1157 articles were retrieved from PubMed, Scopus, Web of Science, and Embase databases. After excluding the duplicates, 978 articles were appraised. 133 articles remained after reading the titles and abstracts of the articles. In the next step, the articles were evaluated regarding methodology, research population, and exclusion criteria, after which 112 articles were omitted, and finally, 21 articles were included in the full-text review. We assessed all included studies using the Quality Assessment of Controlled Intervention Studies checklist. Results: A total of 21 randomized controlled trials met the inclusion criteria. "Physiologic health", "functional health", "psychosocial health", "health knowledge and behavior", and "perceived health" were the domains of nursing outcomes investigated as Patient Education Outcomes in NLCs. Conclusion: Most of the outcomes were linked to lifestyle-related chronic diseases and, further studies are needed to determine the effects of patient education provided in NLCs in terms of family/society health outcomes.